Guadecitabine improved relapse-free survival in high-risk acute myeloid leukemia and myelodysplastic syndrome patients after transplant: phase II results from a single center - Betül Oran; Peter Thall; Amin Alousi; Gheath Al-Atrash; Rohtesh Mehta; David Marin; Partow Kebriaei; Uday Popat; Roland Bassett; Qaiser Bashir; Jin Im; Amanda Olson; et al. (Haematologica)
This phase 2, single-center clinical trial evaluated the efficacy and safety of guadecitabine, with or without donor lymphocyte infusion, following allogeneic stem cell transplantation (allo-SCT) in adult patients with acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). The study had three treatment cohorts based on disease status post-transplant. Cohort 1 included patients with hematological relapse after transplant (n=13). Cohort 2 consisted of patients with minimal residual disease (MRD) detected after transplant (n=18). Cohort 3 compromised of patients in remission without MRD within 100 days post-transplant (n=24). The primary objectives were to achieve morphological complete remission (CR) in cohort 1 and MRD eradication in cohort 2 within six cycles of guadecitabine. Cohort 3 patients received 12 cycles to improve relapse-free survival (RFS).